Sapota-do-solimões (Quararibea cordata): Caracterização físico-química, estabilidade, compostos bioativos e voláteis - Monteiro, Sabrina Sauthier (2017)
Sapota-do-Solimões (Quararibea cordata) is a fruit found in the Amazon region of Brazil consumed only by the local population. The production of vegetable pulp is a viable operation in harvest period and able to serve the consumer at any time of year, even in distant places of origin. It is a fruit still little known worldwide and presents a high agroindustrial potential. Thus, the present work aims to analyze the parts of sapota-do-Solimões (peel, pulp and seeds), the stability of elaborated pulps and the bioactive and volatile compounds of the pulp in different ripening stages. The samples were collected from the city of Tefé-AM in three distinct ripening stages: unripe (U), ripe and collected from the tree (R); and ripe and collected from the ground, i.e. when the fruit fell naturally to the ground from the tree (RG), and transported to Santa Maria-RS. In the first study, the fruits R were used and the biometric parameters, the chemical composition and the mineral content were characterized. In the second, fruits R were pulped and submitted to the treatments: freezing, pasteurization + freezing, refrigeration and pasteurization + refrigeration, physicochemical and microbiological characteristics and bioactive compounds were analyzed in seven different storage times during 180 days. The third study, one comprised pulp analysis (U, R and RG) of biometric parameters, of quality, bioactive compounds, chemical composition, fatty acids and volatile profile. The percentages of peel, pulp and seeds were, respectively, 53.2%, 39.6% and 7.2%. The chemical composition in 100 g of sapota-do-Solimões was 85.01% moisture; 0.79% ash; 0.67% protein; 0.10% lipids, 4.10% dietary fiber; 9.34% carbohydrate and 40.94 calories. Magnesium was the most important mineral in the pulp. In the elaborated pulps, the treatments affected the physical-chemical parameters during the storage. Ascorbic acid remained stable during freezing and total carotenoid levels were maintained in pasteurization + freezing. Total phenols remained stable for up to 150 days and antioxidant activity decreased during storage for all treatments. The pasteurization + freezing treatment, as well as the freezing treatment, maintained pulp quality for 180 days of storage. With the ripening of the sapota-do-Solimões, there was an increase in water activity (0.977-0.996), pH (6.53-7.04), soluble solids (8.53-12.65%), total sugars (4.26-7.98%), reducing sugars (0.99-3.14%), non-reducing sugars (3.11-4.60%), total carotenoids (0.67-1.24 μg/g of pulp). The lipids increased with respect to ripening stage U (0.16%) and RG (0.30%). Eleven fatty acids were detected in the pulps. A total of 86 volatile compounds were identified, of which 57 were found in U fruits, 54 in R fruits and 68 in RG fruits. Methyl and ethyl benzoate esters were found in the RG fruits. There was an increase in terpene compounds; from 0.4% for U fruit to 5.6% for RG fruit. The data showed that the composition of the fruit was influenced by the ripening stage of the pulp.